Mindful Learning Experience Facilitates Mastery Experience Through Heightened Flow and Self-Efficacy in Game-Based Creativity Learning - Yeh, Yu-chu; Chen, Szu-Yu; Rega, Elisa Marie; Lin, Chin-Shan (Frontiers in Psychology, 2019)
To date, game-based learning programs that include comprehensive creativity skills and disposition training are still very limited. The present researchers developed a comprehensive game-based creativity learning program for fifth and sixth grade pupils. Further analysis presented relationship trends between mindful learning experience, flow experience, self-efficacy, and mastery experience. Eighty-three 5th and 6th grade participants undertook the six-week game-based creativity learning program. Upon the completion of experimental instruction, those who scored higher on the concerned variables improved more in self-evaluation of both creativity ability and confidence, than their counterparts. Additionally, path model analysis revealed that mindful learning experience was a powerful predictor of both mastery experience and flow experience; it also influenced mastery experience through flow experience and self-efficacy during game-based creativity learning. The findings support the effectiveness of the game-based learning program developed in this study. Moreover, this study contributes to the theoretical construction of how game-based learning can be designed to facilitate mindful learning experience, flow experience, self-efficacy, and mastery experience during creativity training among pupils. Effective mechanisms include providing rewards for high-quality performance, challenging tasks, free choices of design components, immediate feedback, and idea sharing. The profound theoretical framework proposed in this study provides a valuable approach for creativity instruction through game-based learning or classroom instruction.